Fair allocation of fixed cost in one- and two-stage systems using data envelopment analysis - Faranak Hosseinzadeh Saljooghi; Ali reza Pishgooy; Farhad Hamidi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The fair allocation and distribution of fixed costs in a set of competitive entities is one of the most important management issues. Fair cost allocation between stages is of particular importance.Methodology: Data envelopment analysis plays an important role in evaluating and comparing between units, efficiency and fixed cost allocation between different units. In cost allocation, in addition to the approach of maintaining and increasing efficiency, attention should also be paid to the competitive conditions and cooperation. Since cross-efficiency in data envelopment analysis handles these conditions of competition and cooperation between units well.Findings: In this article, using the improved cross-efficiency and the proposed algorithm, we allocate a unique fixed cost to the units under evaluation in single-stage and two-stage supply chain systems fairly. This method does not have the complexity of calculations of previous methods.Originality/Value: The results of the proposed method have been analyzed on real data, 29 branches of Iranian banks in a one-stage. Cost allocation is obtained uniquely. Then, to generalize the model in a two-stage mode, the data of 24 insurance companies with input, intermediate and output indicators have been used.